Дослідження методів створення покадрової анімації в сучасності - Тараненко, О. В. (ХНУРЕ, 2023)
This work is devoted to the study of methods of creating frame-by-frame animation, as well as ways of implementing these methods. From its creation at the end of the 19th century to the present, classic hand-drawn animation of characters (and not only) has come a long and rich way. It was constantly changing, modernizing and adapting to the challenges of the times it was passing through. But even today, frame-by-frame animation remains a very popular animation technique with a more developed list of methods for its implementation.